Analisis Akuntabilitas Kinerja Instansi Pemerintah Kabupaten Sidoarjo - Saprila Nur Fadila; Gideon Setyo Budiwitjaksono (Universitas Pendidikan Ganesha, 2022)
This study aims to examine the effect of budget goal clarity, accounting control, reporting systems, and human resource quality on accountability of Sidoarjo Local Government performance. All of the Head OPD, Secretaries, Head of Sub Division of Planning and Finance, as well as Staff of Planning and Finance Division in Sidoarjo Local Government Office was selected as population in this study. The sample of this study is 64 respondents selected using probability method with simple random sampling technique. Data analysis in this study used multiple regression analysis methods with SPSS version 26 for windows software application. The result of this study showed that budget goal clarity and reporting system had a significant effect on accountability of Sidoarjo Local Government performance, while the accounting control and human resource quality had no significant effect on accountability of Sidoarjo Local Government performance.